Incidence of adverse drug reactions in patients taking anti-tuberculosis treatment - Gosai, Tushar R.; Balat, Jayesh D.; Trivedi, Hiren R. (International Journal of Advances in Medicine, 2019)
Background: High incidence of infection has caused a large number of morbidity and mortality which is partly due to serious adverse reactions induced by Anti-Tuberculosis (Anti-TB) drugs. In present prospective study an attempt is made to estimate the incidence and risk factor for ADRs among patients treated for tuberculosis. Methods: All the new patients starting their treatment with selected six DOT center were enrolled in study. All patient’s complete clinical history was recorded. They were followed regularly for occurrence of ADR till end of their treatment. Results: Total of 108 patients (67 male and 41 female) had taken and completed their treatment during the study period (March 2007 - April 2008) and were observed for occurrence of ADR during their treatment period. Out of total108, 28 patients (25.9%) experienced one of the ADR, out of 28 patients, 12 (42.85%) patients developed GIT intolerance, and hepatitis was seen in 8 (28.57%) patients, while 4 (14.48%) patients developed skin reactions. Only 3 (7.14%) patient developed dizziness and loss of balance, which was relieved by reduction of dose of streptomycin. Conclusions: With close monitoring and on time action, RNTCP DOTs regimens can be safely and successfully administrated.